The acute effects of a short technique-intense training period on side-foot kick performance among elite female soccer players - Carlsson, M.; Isberg, J.; Nilsson, J.; Carlsson, T. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Previously, it was shown that elite soccer teams were 24% more likely to win matches if their passing effectiveness were increased by 1%. However, research interventions aiming to improve passing performance are scarce. The current study aimed to investigate the effect of a short technique-intense training period on side-foot kick performance among elite female soccer players. METHODS: Four side-foot kick tests were completed before and after a training period: kicking a stationary ball using match-relevant (SBRS) and maximal ball speed (SBMS), passing the ball on the move using match-relevant ball speed (RBRS), and repeated side-foot kicks onto a rebound-box with continuously increasing passing distance (RRB). The players were assigned to either the intervention group or the control group. The training intervention consisted of six 55-min training sessions with five side-foot kick exercises. Within-group and between-group differences were investigated using paired-samples t-test and Mann-Whitney U test, respectively. RESULTS: The intervention group improved the performance in the RBRS and RRB tests (both P<0.05), but no differences were found for the SBRS and SBMS tests (both P>0.05). No improvements were found for the control group independent of test condition (all P>0.05). Significant between-group differences were found for the RBRS and RRB tests (both P<0.05), whereas no differences were found for the SBRS and SBMS tests (both P>0.05). CONCLUSIONS: The fundamental soccer skill of passing a moving ball was improved in elite female soccer players by a short technique-intense training period.